Active learning attitudes in pharmacy education in Klang Valley / Mohd Khairol Amir Mohd Khotib - Mohd Khotib, Mohd Khairol Amir (2009)
This study was set out to investigate current active learning attitudes in pharmacy education in Klang Valley, Selangor, Malaysia. Cross-sectional descriptive design and convenience survey methods were used. The sample consisted of 145 students from UiTM and UM who completed the questionnaires. Active learning attitudes of the students were assessed with a modification of attitude surveys. Nineteen active learning items were analyzed and classified into four topics: participation in class, learning strategies, self-efficacy and motivation. All four topics of both universities are not significantly different. It can be concluded that students from both universities, UiTM and UM demonstrated a positive attitude toward active learning, believed it helped (or would helped) th